Question
upstudy study bank question image url

Solve for all possible values of x . \[ \sqrt{3-x}=x-3 \]

Ask by Murray Herrera. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x=3 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Extra Insights

To solve the equation \( \sqrt{3-x} = x - 3 \), we first square both sides to eliminate the square root: \[ 3 - x = (x - 3)^2 \] Expanding the right side gives: \[ 3 - x = x^2 - 6x + 9 \] Rearranging all terms to one side, we have: \[ 0 = x^2 - 6x + 9 + x - 3 \] This simplifies to: \[ 0 = x^2 - 5x + 6 \] Factoring the quadratic, we find: \[ 0 = (x - 2)(x - 3) \] Setting each factor to zero gives the possible solutions: \[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \] \[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \] Next, we need to verify if these solutions satisfy the original equation. For \( x = 2 \): \[ \sqrt{3 - 2} = 2 - 3 \quad \Rightarrow \quad \sqrt{1} = -1 \quad \text{(not valid)} \] For \( x = 3 \): \[ \sqrt{3 - 3} = 3 - 3 \quad \Rightarrow \quad 0 = 0 \quad \text{(valid)} \] Thus, the only solution is: \[ \boxed{3} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy